Decontamination of chlorobenzene by electrochemical method - Abdul Jalil, Aishah; Idris, Ani; Triwahyono, Sugeng; Tokuda, Masao (2004)

(untitled)
A new decontamination system of chlorobenzene was carried out by electrolysis of an N,N-dimethylformamide (DMF) solution containing monochlorobenzene as a substrate and supporting electrolyte in a one-compartment cell fitted with a platinum cathode and a metal anode. In this system, monochlorobenzene was dechlorinated to benzene where the progress of the reaction was analyzed by gas chromatography. Effect of temperature, type of anode material and solvent was investigated and it was also found that the rate and current efficiency for the benzene production were greatly improved when naphthalene was used as a mediator. In the presence of naphthalene, the reduction of chlorobenzene occurs indirectly compared to its direct reduction at the platinum cathode to give complete dechlorination.